2009
DOI: 10.1073/pnas.0812757106
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the effect of estrogen and testosterone on economic behavior

Abstract: Existing correlative evidence suggests that sex hormones may affect economic behavior such as risk taking and reciprocal fairness. To test this hypothesis we conducted a double-blind randomized study. Two-hundred healthy postmenopausal women aged 50 -65 years were randomly allocated to 4 weeks of treatment with estrogen, testosterone, or placebo. At the end of the treatment period, the subjects participated in a series of economic experiments that measure altruism, reciprocal fairness, trust, trustworthiness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 32 publications
8
147
2
1
Order By: Relevance
“…A previous between-subjects study with post-menopausal women found no effect of 4 weeks of T treatment on various economic decisions including ultimatum acceptance thresholds (Zethraeus et al, 2009). Two other studies have administered T to participants in the ultimatum game with mixed evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous between-subjects study with post-menopausal women found no effect of 4 weeks of T treatment on various economic decisions including ultimatum acceptance thresholds (Zethraeus et al, 2009). Two other studies have administered T to participants in the ultimatum game with mixed evidence.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies investigating the effects of exogenous manipulations of T on economic behavior, and most have focused on female, rather than male behavior M A N U S C R I P T ACCEPTED MANUSCRIPT 4 (Zethraeus et al, 2009;Bos et al, 2010;Eisenegger et al, 2010;van Honk et al, 2012;Boksem et al, 2013). Some exceptions of recent work involving T administration in healthy men include Zak et al (2009), who report suggestive evidence that it decreased generosity, 1 Wibral et al (2012) who found that it reduced lying, Carré et al (2015) who showed that it impaired socio-cognitive ability only in subjects with low 2D4D or low psychopathic traits, Cueva et al (2015) who found that it increased risk-taking in an investment task, and Carré et al (2016) who found that it led to greater aggression only in subjects scoring high in trait dominance or low in trait self-control.…”
Section: Introductionmentioning
confidence: 99%
“…Zethraeus et al (2009) examine 200 post-menopausal women in a double-blind study. Participants were given either estradiol (2 mg), testosterone (40 mg) or a placebo daily for a four week period.…”
Section: Introductionmentioning
confidence: 99%
“…This review focuses on gender as a social sciences phenomenon rather than an equally interesting and important focus in the biological sciences on the sex dimorphic effects of hormones, such as testosterone, that affect many dimensions of human behavior (2,3). Exposure and production of hormones construct the biological differences in males and females that underlie social discourses of gender (4).…”
mentioning
confidence: 99%